MANDAL COMMISSIONI AND THE FUTURE OF DALITS: . - George, Dominic (Journal of Dharma, 1991)
Socially sensitive Indian citizens must have been rather shocked, I presume, by the quite viplent response to the Government Order (G.O.), issued by the V.P. Singh~mi!:listry on the Mandai Commission Report on 13th August, 1990. Why was there such a response? Was the acceptance by the V.P. Singh government, of a very small part of the varied recommendations of the Mandai Commission, doing an injustice to the forward communities of India? Will Mandai Commission recommendations get really Implemented in this country? And if they are implemented, how are they likely to influence the 'dalits' of India? These and related questions will be explored in this .article.